Magnetite Surface Modification with Silica and Its Application as Adsorbent of Heavy Metal Ion Nickel and Manganese - Diah Mahmuda (Eksergi, 2022)
This study aims to synthesize magnetite by a co-precipitation method. The prepared adsorbent magnetite coated by silica for the efficient removal nickel and manganese ions from the aqueous solutions. The prepared samples have characterized by several techniques like FTIR spectroscopy, XRD, and TEM. Surface modification causes the magnetite ability of removing metals ions increasing more than 98%. Preliminary results indicate that magnetite coated silica may be used as an adsorbent for removal of nickel and manganese ions from wastewater.